Development of artificial intelligence-based interactive learning media to enhance students' critical thinking skills - Ferry Irawan; Rival Hanip; Minuk Riyana; Hernita A (Universitas Negeri Yogyakarta, 2026)
The rapid advancement of Artificial Intelligence (AI) has significantly transformed educational practices. In biology education, many concepts remain abstract and difficult to understand through conventional instruction, leading to low conceptual understanding and inadequate critical thinking skills among students. Therefore, this study aimed to develop an Artificial Intelligence-based interactive learning media and evaluate its validity, practicality, and effectiveness in enhancing senior high school students' critical thinking skills in biology learning. This research employed the Research and Development (RD) method using the ADDIE instructional design model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The participants included biology education experts, instructional media experts, biology teachers, and Grade XI students. The research instruments consisted of expert validation sheets, teacher and student practicality questionnaires, observation sheets, and critical thinking tests. Data were analyzed using descriptive statistics, Aiken's V, Cronbach's Alpha, normalized gain (N-Gain), paired-sample t-test, and Cohen's d effect size. The developed media integrates AI-assisted tutoring, adaptive quizzes, animated biological simulations, virtual laboratory activities, personalized feedback, and learning analytics. Expert validation results indicated that the media achieved a very high level of validity (94.2%). Practicality evaluation showed positive responses from both teachers (93.7%) and students (89.3%), indicating that the media was highly practical for classroom implementation. Furthermore, the effectiveness test showed significant improvement in students' critical thinking skills, with an average N-Gain score of 0.72, categorized as great improvement. Statistical analysis confirmed significant differences between pre-test and post-test scores (p 0.001) with a large effect size. The findings suggest that integrating Artificial Intelligence into biology learning media provides meaningful learning experiences by facilitating personalized instruction, immediate feedback, and interactive visualization of complex biological concepts. Consequently, AI-based interactive learning media can serve as an effective educational innovation to improve biology learning outcomes and foster higher-order thinking skills.